Energy demand and fuel substitution model for urban domestic sector (for electricity planning) a case of Nepal - Rokaya, K. B. (1991)
Nepal imports all of its petroleum product requirements which is account for 72 percent of her total energy consumption. The urban domestic household sector relies heavily on petroleum products with kerosene, which is mainly used for household cooking, having the major share. This heavy reliance of the urban household sector on imported kerosene oil for cooking is coating the country too much in terms of foreign currency reserve, trade deficit, fuel dependency and uncertainty in fuel supply. On the other hand, the vast hydropower potential available in the country remains virtually unutilized. In this study, an analytical model has been developed for energy demand projections and fuel substitution studies for urban domestic sector. The model can be used to update the electric load forecast and consequently the electricity generation expansion plan. The model has been applied to make energy demand projections and fuel substitution studies for urban household cooking in Nepal. The impact of improving the efficiency of kerosene stove and electric stove on the energy demand for cooking has also been looked into the model simulation.
The results reveal that the potential for substituting kerosene oil with electricity in urban cooking is very high. The change in the electric load forecast for Integrated Nepal Power System due to kerosene oil substitution is very significant. The availability of vast hydropower potential makes this substitution possible. The total cost of supplying energy for urban household cooking has been calculated for the different scenarios considered. The economic viability of substitution of imported kerosene oil with indigenous hydroelectricity depends on the price of kerosene, vis-a-vis the cost of developing hydroelectricity.
Thesis (Ph.D Energy Engineering)--University of the Philippines Diliman.
Typescript (photocopy).
Keywords: Energy consumption -- Nepal; Energy policy -- Nepal; Fuel switching -- Simulation methods; Petroleum as fuel